2023
DOI: 10.1136/bmjopen-2022-066445
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported burden of myasthenia gravis: baseline results of the international prospective, observational, longitudinal real-world digital study MyRealWorld-MG

Abstract: ObjectivesMyasthenia gravis (MG) is a rare, chronic, autoimmune neuromuscular disease which can affect functional and mental aspects of health and health-related quality of life (HRQoL). This study aims to obtain detailed knowledge of the impact of MG on HRQoL in a broad population from the perspective of the patient.DesignProspective, observational, digital, longitudinal real-world study.SettingAdult patients with MG from seven countries (USA, Japan, Germany, UK, Italy, Spain and Canada) downloaded a mobile a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 38 publications
(74 reference statements)
0
11
0
Order By: Relevance
“…A patient-centred approach is important in gMG treatment. [EQ-5D-VAS]) [3,16,22] to determine patient satisfaction with symptom state and treatment can be used effectively in this setting.…”
Section: Grade B Telemedicinementioning
confidence: 99%
See 2 more Smart Citations
“…A patient-centred approach is important in gMG treatment. [EQ-5D-VAS]) [3,16,22] to determine patient satisfaction with symptom state and treatment can be used effectively in this setting.…”
Section: Grade B Telemedicinementioning
confidence: 99%
“…Most patients with myasthenia gravis (MG) first present with ocular symptoms only; however, approximately 80% will have gMG within 2 years of initial disease onset [2]. gMG is classified by degree of muscle weakness, which, along with other symptoms of the disease, may vary greatly among individuals and fluctuate over time [1][2][3][4][5][6]. This variation in symptoms, combined with infrequent and isolated evaluations, means accurate tracking of symptom state and full comprehension of disease burden is difficult [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 15% of patients are refractory to standard therapies and are often dependent on costly treatments such as IVIg and TPE 3 . Real-world studies have shown that over 40% of patients with MG have unacceptable disease control 8 and MG is known to have a significant impact on quality of life 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, patients with gMG report lower health-related quality of life (HRQoL) than in the general population [ 8 , 9 ]. Several disease-specific and generic instruments have been validated in patients with gMG that can be used to assess patients’ symptom severity, functional status, and HRQoL.…”
Section: Introductionmentioning
confidence: 99%